Interaction of Escherichia coli B and B/4 and Bacteriophage T4D with Berea Sandstone Rock in Relation to Enhanced Oil Recovery - Chang, Philip L. (1984)
Much research and development is needed to recover oil reserves presently unattainable, and microbially enhanced oil recovery is a technology that may be used for this purpose. To address the problem of bacterial contamination in an oil field injection well region, we connected each end of a Teflon-sleeved Berea sandstone rock to a flask containing nutrient medium. By inoculating one flask with Escherichia coli B, we could observe bacterial growth in the uninoculated flask resulting from the transport and establishment of cells across the rock. Differences in bacterial populations occurred depending on whether bacteriophage T4D was first adsorbed to the rock. The results of these experiments indicate that the inhibition of bacterial establishment within a rock matrix is possible via lytic interaction. Some nonlytic effects are also implied by experiments with B/4 cells, which are T4D-resistant mutants of E. coli B. A 10 to 40% retention of T4 by the rock occurred when it was loaded with 10(5) to 10(6) PFU. We also describe a lysogenic system for possible use in microbially enhanced oil recovery techniques.